Multifaceted effects of host country language proficiency in expatriate cross-cultural adjustments: a qualitative study in China. Issue 13 (19th July 2016) - Zhang, Ling Eleanor; Peltokorpi, Vesa
Abstract : While expatriates often face language barriers in host countries, relatively little research has focused on the influence of host country language proficiency on cross-cultural adjustment. We drew on social identity theory and conducted an interview-based study with 70 expatriates and their host country national (HCN) colleagues to provide a contextual account of host country language proficiency's effects on work and non-work-related adjustment in China. Our findings suggest that expatriate host country language proficiency has multifaceted effects on expatriates' HCN interaction, social support, and network-related work and non-work adjustment.